Time-to-Positivity of Blood Cultures in Children With Sepsis - Dierig, Alexa; Berger, Christoph; Agyeman, Philipp K. A.; Bernhard-Stirnemann, Sara; Giannoni, Eric; Stocker, Martin; Posfay-Barbe, Klara M.; Niederer-Loher, Anita; Kahlert, Christian R.; Donas, Alex; Hasters, Paul; Relly, Christa; et al. (Frontiers in Pediatrics, 2018)
Background Blood cultures are essential for the diagnosis and further appropriate treatment in children with suspected sepsis. In most hospitals, children will be empirically treated or closely monitored for at least 48 hours awaiting results of blood cultures. Several studies have challenged the optimal duration of empiric treatment in the era of continuously monitored blood culture systems. The aim of our study was to investigate time-to-positivity (TTP) of blood cultures in children with proven sepsis. Methods The Swiss Pediatric Sepsis Study prospectively enrolled children 0–16 years of age with blood culture positive sepsis between September 2011 and October 2015. TTP was prospectively assessed in 6 participating academic pediatric hospitals by fully automated blood culture systems. Results In 521 (93%) of 562 bacteremia episodes (493 children, median age 103 days, range 0 days–16.9 years) a valid TTP was available. Median TTP was 12 hours (IQR 8-17 hours, range 0-109 hours). By 24, 36 and 48 hours, 460 (88%), 498 (96%) and 510 (98%) blood cultures, respectively, were positive. TTP was independent of age, sex, presence of comorbidities, site of infection and severity of infection. Median TTP in all age groups combined was shortest for group B streptococcus (8.7 hours) and longest for coagulase-negative staphylococci (16.2 hours). Conclusion Growth of bacteria in blood cultures is detectable within 24 hours in 9 of 10 children with blood culture-proven sepsis. Therefore, a strict rule to observe or treat all children with suspected sepsis for at least 48 hours is not justified.